Effect of Transformational Leadership on Employee Performance: The Case of East Wallaga Zone Public Sectors - Gudata Abara; Girma Tamiru Wakjira (The Indonesian Institute of Science and Technology Research, 2026)
This study investigates the influence of transformational leadership on employee performance within public sector organizations in the East Wallaga Zone, Oromia, Ethiopia. Utilizing an explanatory and descriptive research design, the study employed a mixed-methods approach to collect data from a sample of 300 employees across various zonal sectors. Systematic sampling was used to ensure representativeness from a total population of 2,175. The data were analyzed using SPSS through descriptive statistics and inferential tools, including Pearson correlation and multiple regression. Findings reveal a significant positive correlation between transformational leadership dimensions and employee performance. Regression results indicated that leadership behaviors account for 83.7% of the variance in performance (R2=0.837). Notably, Contingent Reward (B=1.293) and Intellectual Stimulation (B=0.433) emerged as the most potent predictors. The study concludes that supervisors who employ idealized influence and inspirational motivation significantly enhance employee engagement. Recommendations include institutionalizing leadership development programs and refining merit-based recognition systems to sustain public sector efficiency.